2007
DOI: 10.1007/s00192-007-0504-8
|View full text |Cite
|
Sign up to set email alerts
|

The effects of bilateral caudal epidural S2–4 neuromodulation on female sexual function

Abstract: This is a pilot study to evaluate the effects of caudal epidural S2-4 neuromodulation on female sexual function in a population of women with voiding dysfunction. We prospectively studied 36 consecutive female patients who underwent caudal epidural sacral neuromodulation. Patients received the Female Sexual Function Index (FSFI) questionnaire preoperatively and 6 months postoperatively. Six months after permanent implantation, the overall score on the FSFI improved by 52% (p = 0.05). Results were better in pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 10 publications
0
17
0
1
Order By: Relevance
“…The permanent InterStim® implant has been shown to provide benefit to those suffering from refractory overactive bladder and retention. Early reports have shown that InterStim® neuromodulation may also provide benefit for women with female sexual dysfunction …”
Section: Introductionmentioning
confidence: 99%
“…The permanent InterStim® implant has been shown to provide benefit to those suffering from refractory overactive bladder and retention. Early reports have shown that InterStim® neuromodulation may also provide benefit for women with female sexual dysfunction …”
Section: Introductionmentioning
confidence: 99%
“…Another study on the effects of SNM for LUTS on female sexual function was carried out by Zahibi et al [24]. A characteristic of this study was that a large proportion of the patients had pelvic pain as well as LUTS.…”
Section: Discussionmentioning
confidence: 99%
“…However, one attractive hypothesis is that widespread activation of both ascending and descending activity in the spinal cord may strengthen synaptic activity in lumbosacral motor centers through Hebbian mechanisms, including walking, micturition, and defecation. Recent unconfirmed reports (46,123,170,278) suggest epidural stimulation may improve sexual function, another programmed activity of the lower spinal cord. If confirmed, epidural stimulation is likely to become a popular approach for this purpose.…”
Section: Epidural Spinal Cord Stimulationmentioning
confidence: 98%